Tau approximate solution of weakly singular Volterra integral equations with Legendre wavelet basis. Issue 7 (3rd July 2017) - Pourgholi, Reza; Tahmasebi, Ali; Azimi, Ruhangiz
ABSTRACT: In this paper, a spectral Tau method based on Legendre Wavelet basis is proposed. For this purpose we present a stable operational Tau method based on Legendre Wavelet basis. This method provides an efficient approximate solution for weakly singular Volterra integral equations by using reduced set of matrix operations. An error estimation of the Tau method is also introduced. Finally we demonstrate the validity and applicability of the method by numerical examples.